PERAN LEMBAGA INTERNASIONAL DALAM PENEGAKAN HUKUM HUMANITER: EVALUASI EFEKTIVITAS MISI PEMELIHARAAN PERDAMAIAN PBB DAN PALANG MERAH INTERNASIONAL DALAM MENANGGULANGI PELANGGARAN HUKUM PADA KONFLIK BERSENJATA - Andes Sebayang; Abdul Majeed Abdullah Alharbi, Kadep Faljuang Sesko TNI, Iwan Setiawan, Aqsha Erlangga (JOURNAL OF LAW AND NATION, 2025)
The enforcement of international humanitarian law during armed conflict plays a crucial role in protecting human rights and ensuring the safety of individuals affected by war. International organizations such as the United Nations (UN) and the International Red Cross have critical missions in peacekeeping and conflict resolution, which are essential to upholding humanitarian law on the ground. This article aims to evaluate the effectiveness of UN peacekeeping missions and the role of the International Red Cross in addressing violations of humanitarian law in conflict zones. Using a qualitative approach, the article analyzes the challenges, successes, and collaborative roles of both institutions in safeguarding humanitarian law and improving conditions for war victims. The findings of this study are expected to provide insights into the role of international institutions in maintaining global peace and the relevance of conflict resolution efforts based on humanitarian law.